Fractional Characteristics of Heavy Metals Pb, Zn, Cu, and Cd in Sewer Sediment from Areas in Central Beijing, China - Haiyan Li; Mingxiu Wang; Wenwen Zhang; Ziyang Zhang; Xiaoran Zhang (Journal of Chemistry)
To identify the distribution of heavy metals in sewer sediments and assess their potential harmfulness to the environment and human health, the occurrence of Pb, Zn, Cu, and Cd in the sewer sediment of six functional areas and two streets in an inner-city suburb of Beijing, China, was investigated by using a sequential extraction procedure. Results show that the concentrations of Cu, Zn, Cd, and Pb vary between 50 and 175, between 80 and 180, between 0.75 and 2.5, and between 20 and 110 mg/kg, respectively, and Fe-Mn oxide fraction is significant for all metals in sampling areas. Pollution assessment shows that 1–2% of Cu at Chegongzhuang Street and 1–3% of Zn at Fuwai Street in the exchangeable fractions are of low risk. 10–25% of Cd at six functional areas indicates medium risk. 40–60% of Pb at Fuwai Street existing in the exchangeable fractions is of high to very high risk. The sum of these metals associated with exchangeable, carbonate bound, and Fe-Mn oxide fractions is quite high; however, these three fractions represent the proportion of heavy metals that can be remobilized by changes in environmental conditions.